Interculturality in Latin American Rural Bilingual Education: A Systematic Literature Review - Diana Marcela Duque Salazar; María Alejandra Tangarife Loaiza; Ángela Patricia Velásquez Hoyos (Profile: Issues in Teachers' Professional Development)
This systematic literature review examines the panorama of interculturality in rural contexts of bilingual education in Latin America. It aims to provide a comprehensive overview of the current state of knowledge in Latin America and identify key themes, challenges, and gaps in the field. The review highlights the importance of recognizing and valuing linguistic and cultural diversity, particularly in marginalized rural communities. It also discusses the lack of adequate resources and educational policies as significant challenges to promoting intercultural bilingual education in these contexts. The findings underscore the need for further research and the development of effective strategies to enhance intercultural understanding and bilingual education in Latin American rural areas.